Pola Asuh Orangtua Single Parents - Nugrahani, Rizka Fibria; Fitri, Wulan Charisma (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Abstract: Parenting is the behavior and attitude of guardian parents in fostering child survival, development and providing protection to children equally physically, socially or spiritually to create children with personality. Parenting is an environmental activity that includes a variety of special behaviors that work together individually and simultaneously in influencing children's behavior (Silalahi and Minamo, 2010: 164). Single Parent is a fact that is increasingly taken for granted in modern society, people Older people who are forced to experience it either because they are divorced or their spouse dies do not need to sink for a long time because they are able to learn many things, such as the mass media or people who experience it (Meyland, 2019).Qualitative research is a scientific research, which aims to understand a phenomenon in a natural social context by prioritizing a process of in-depth communication interaction between the researcher and the phenomenon being studied. (Haris Herdiansyah, 2015). Based on research findings in the field, single parent parenting styles for each subject have different parenting styles, and there are 3 types of parenting styles. by something. Where these parents have certain reasons and goals. the results of the study showed that the three single parent subjects had similarities and differences in parenting. These similarities and differences are found in each type of parenting, namely authoritarian parenting, democratic parenting, and permissive parenting.According to several theories related to the problem under study, namely the Parenting Style of Single Parents in Purwodadi Donomulyo Village, Malang. There are several unique parenting styles for each subject obtained from the interview results. And based on several parenting styles, it was concluded that the three subjects had similarities and also differences in parenting styles, both authoritarian, democratic, and permissive parenting styles.